The conservation treatment and visual reintegration of a major repair of a painted portrait photograph of the Reverend William Henry Browne. Issue 2 (2nd July 2016) - Tait, Robin; Gomez Lobon, Mar
Abstract : This paper describes an evidence-based treatment of a composite painted and photographic portrait, an area which remains underrepresented in conservation literature. Conservation treatment was undertaken on a painted photographic portrait of the Reverend William Henry Browne (1800–1877), c. 1860s. Browne was the Rector of St John's Church and Archdeacon of Launceston, and a prominent figure in the colonial days of northern Van Diemen's Land. The portrait was painted with watercolour, pastel and gouache over a salted paper photographic print, lined onto a fine cotton fabric and mounted on a strainer. It had suffered severe damage resulting in a large loss of both the paper and fabric supports comprising a large section of the sitter's head. The conservation treatment involved unstretching, removal of the fabric lining, a blotter 'wash', lining onto a new cotton cloth similar to the original and stretching the work back onto its original strainer. The large loss was fully reconstructed with imitative reintegration techniques, using a small photograph of the sitter found in a 1914 pamphlet as a reference. This treatment involved combining the skills of both paper and paintings conservators, as the object is a technical combination of both a photograph and a work of art on paper, and is presented as a painting, i.e. lined with cloth, mounted on a wooden strainer and likely framed. After treatment the quality of the work was revealed, which instigated further work into a plausible attribution.